IMPLEMENTASI MANAJEMEN MUTU SUMBER DAYA MANUSIA DI MTS NURUS SALAM - Wijaya, Candra; Junani, Bening Luhur (Dharmas Education Journal (DE_Journal), 2023)
Education is very important in improving the quality of human resources (HR), quality education is a hope for the whole community. The formulation of the problem that the author does is how to implement quality management and implement quality management standards at MTs Nurus Salam schools. The methodology in this study uses a qualitative descriptive research type, this study uses interview, observation, and documentation data collection techniques. Based on the results of the research, the implementation of quality management in MTs Nurus Salam schools, the principal has done something positive, such as: seeking the effectiveness of the learning process by motivating teachers and teachers also increasing their competence. The conclusion from the research is that education quality management is carried out by MTs Nurus Salam with the quality of implementation in accordance with national standards. The role of madrasas in balancing the process and results of education. In the end, students will grow into quality Muslim individuals.